PERANCANGAN SISTEM INFORMASI MANAJEMEN SUMBER DAYA MANUSIA BERBASIS WEBSITE MENGGUNAKAN METODE SCRUM (STUDI KASUS: PT IDS TEKNOLOGI INDONESIA) - Gilang Chandra Syahputra (2023)
The presence of digital systems in the era of the industrial revolution 4.0 has helped many business processes that occur within companies, especially in the field of staffing. All business processes in the company can now be digitized so that data processing can be more effective and efficient. The object of this research is PT IDS Teknologi Indonesia, which has not been supported by an information system which has resulted in ineffective data processing in the human resources department. The processing of attendance data, application for leave, and claims is still carried out using excel documents. Reporting is still done by recapitulating data, which takes a long time and requires accuracy. These things seriously impede the effectiveness and efficiency of PT IDS Teknologi Indonesia, especially in the human resource development section, and form the basis for research and design of human resource management information systems, which are expected to make data processing at PT IDS Teknologi Indonesia more effective and efficient.